The Impact of Educational Technology on Special Education: A Comparative Study - Dr. Sonu Grewal (Universal Research Reports, 2019)
This research explores the impact of educational technology on special education, focusing on how digital tools and resources enhance learning outcomes for students with disabilities. The study was inspired by the researcher’s personal experience during her Master’s in Education, when she had a blind roommate and classmate who used a tape recorder to record lectures and later transcribed them into Braille. This observation led to a deeper inquiry into how advancements in educational technology can provide more accessible and efficient learning solutions for students with special needs. The study compares traditional teaching methods with technology-enhanced approaches, analyzing their effectiveness in supporting individualized learning plans, improving engagement, and fostering independence. Using qualitative and quantitative methods, including surveys, interviews with educators and parents, and analysis of student performance data, the research highlights the significant benefits of educational technology for students with disabilities while addressing challenges like inadequate teacher training and limited technology access. Recommendations are made for more effective integration of technology into special education settings to maximize its potential and mitigate barriers.